Core training elicits greater improvements than flexibility training in jumping lotus kick performance and physical attributes of Tai Chi athletes: A randomized controlled trial - Feng Li; Wenyan Yue; Hezhi Xie; Huiping Gong (PLoS ONE, 2025)
Tai Chi’s intricate, balance-intensive techniques, such as the Jumping Lotus Kick (JL Kick), demand both core stability and flexibility. Despite their importance, direct empirical comparisons of these training effects on Tai Chi performance remain limited. This study aimed to compare the impacts of an eight-week core stability regimen versus flexibility training on JL Kick proficiency and related physical attributes in Tai Chi athletes. In this randomized controlled trial, thirty-nine male athletes (ages 17–21) were allocated into core stability (n = 13), flexibility (n = 13), and control groups (n = 13). Performance metrics were assessed at baseline, midpoint, post-intervention, and at 12-week follow-up to capture both immediate and sustained effects. Core stability training yielded notable improvements in JL Kick rotation (ES = 1.2), core strength (Hanging Leg Raises, ES = 1.39), and dynamic balance (Y Balance Left, ES = 1.32), surpassing flexibility training, which primarily enhanced range of motion (Sit and Reach, ES = 1.44) without significant impact on JL Kick performance. Positive correlations between core strength, dynamic balance, and JL Kick performance (r = 0.45–0.68, p < 0.01) highlight core stability’s essential role in Tai Chi proficiency. These findings support core stability training as a superior approach to flexibility training for advancing complex Tai Chi movements, with direct implications for optimizing athletic conditioning in Tai Chi and similar martial arts disciplines. These findings advocate for the inclusion of core stability-focused regimens to enhance performance outcomes in dynamic, balance-dependent techniques.